SOSIALISASI KEWIRAUSAHAAN DIGITAL UPAYA PENINGKATAN INCOME PENERIMA KPR SUBSIDI DI PAGUYUBAN CITRA MAYANG ASRI - Azizi, Muhammad Hakim; Cahyanti, Avrilia Nur (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
Many citizens have not utilized technology to be more productive in developing skills in the field of entrepreneurship. The purpose of the socialization program to the community is expected to provide motivation and offer opportunities for entrepreneurship by utilizing digital technology and providing knowledge on how to start and develop a digital business so that it can increase household income in the Citra Mayang Asri community. The method used in this service begins with identifying needs and interests related to digital entrepreneurship, then lectures and discussions are carried out in understanding digital entrepreneurship, and finally evaluating activities to determine the level of understanding of participants. The results of this dedication showed a positive response and succeeded in achieving the main goal. The high enthusiasm and commitment of participants to start a digital business is the main indicator of the success of this activity.